2022
DOI: 10.3389/fbioe.2022.907611
|View full text |Cite
|
Sign up to set email alerts
|

Force-Bioreactor for Assessing Pharmacological Therapies for Mechanobiological Targets

Abstract: Tissue fibrosis is a major health issue that impacts millions of people and is costly to treat. However, few effective anti-fibrotic treatments are available. Due to their central role in fibrotic tissue deposition, fibroblasts and myofibroblasts are the target of many therapeutic strategies centered primarily on either inducing apoptosis or blocking mechanical or biochemical stimulation that leads to excessive collagen production. Part of the development of these drugs for clinical use involves in vitro presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…For instance, a study by Scholp et al (2022) demonstrated how bioreactors can be utilized to evaluate drug response, toxicity, and pharmacokinetics using humanderived cells or tissues. By mimicking physiological conditions, bioreactors offer a more relevant context for assessing the safety and efficacy of potential therapeutics, potentially reducing the reliance on animal models [288][289][290].…”
Section: Bioreactorsmentioning
confidence: 99%
“…For instance, a study by Scholp et al (2022) demonstrated how bioreactors can be utilized to evaluate drug response, toxicity, and pharmacokinetics using humanderived cells or tissues. By mimicking physiological conditions, bioreactors offer a more relevant context for assessing the safety and efficacy of potential therapeutics, potentially reducing the reliance on animal models [288][289][290].…”
Section: Bioreactorsmentioning
confidence: 99%